The Digital Era: Transformation of Elementary School Students' Character through Social Media Interaction - Ainun Jariah; Sukron Fujiaturrahman; Syafruddin Muhdar (UIN Siber Syekh Nurjati Cirebon, 2024)
AbstractThe digital age presents significant challenges and roles in molding the character of elementary school students through social media. Today's youth are exposed to diverse information and interactions via online platforms, presenting new challenges in instilling positive values, attitudes, and behaviors. This study aims to explore how social media influences the character formation of elementary school students in the digital age. Employing a qualitative method with a phenomenological approach, the research involves 27 sixth-grade elementary students, along with teachers and parents as informants. Research tools include observation sheets illustrating social media's influence on character formation and interviews with teachers and parents. The research findings indicate that social media plays a significant role in shaping students' character. Most students demonstrate positive attitudes toward character values potentially influenced by social media, including time discipline, creativity, independence, responsibility, environmental awareness, a strong social spirit, and a high curiosity for new experiences. Keywords: digital age, social media, student’s character. AbstrakEra digital menimbulkan tantangan dan peran yang besar dalam membentuk karakter siswa sekolah dasar melalui media sosial. Anak-anak saat ini terpapar berbagai informasi dan interaksi melalui platform online, yang menciptakan tantangan baru dalam menanamkan nilai-nilai, sikap, dan perilaku positif. Penelitian ini bertujuan untuk mengeksplorasi bagaimana media sosial memengaruhi pembentukan karakter siswa sekolah dasar di era digital. Dengan menggunakan metode kualitatif dan pendekatan fenomenologis, penelitian melibatkan 27 siswa sekolah dasar kelas enam, serta guru dan orang tua sebagai informan. Instrumen penelitian meliputi lembar observasi yang menggambarkan pengaruh media sosial pada pembentukan karakter dan wawancara dengan guru dan orang tua. Hasil penelitian menunjukkan bahwa media sosial memiliki peran signifikan dalam membentuk karakter siswa, dengan sebagian besar menunjukkan sikap positif terhadap nilai-nilai karakter yang mungkin terpengaruh oleh penggunaan media sosial meliputi: religiusitas, toleransi, moral yang baik, disiplin waktu, kreativitas, kemandirian, tanggung jawab, kepedulian terhadap lingkungan, semangat sosial yang kuat, dan rasa ingin tahu yang tinggi terhadap hal-hal baru.Kata kunci: era digital, media sosial, karakter siswa.